2021
DOI: 10.1002/chem.202101223
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced 2D Chiral Crystallization of Pentahelicene Propellers and Their Planarization into Nanographenes

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
(35 reference statements)
2
11
0
Order By: Relevance
“…More recently, Ernst et al have used STM to image the structures formed by trispentahelicene enantiomers on Au(111). 25 In that system, the adsorbates are large enough that their absolute chirality can be determined from the STM images. This reveals ordered 2D domains in which the ratio of enantiomers is 2:1, as observed in this work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Ernst et al have used STM to image the structures formed by trispentahelicene enantiomers on Au(111). 25 In that system, the adsorbates are large enough that their absolute chirality can be determined from the STM images. This reveals ordered 2D domains in which the ratio of enantiomers is 2:1, as observed in this work.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Ernst et al has identified a 2D system that forms an ordered structure with unequal numbers of enantiomers in each unit cell . Trispentahelicene has a structure mimicking a three bladed propeller and exists in enantiomeric forms labeled M- and P-.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the Co-DPP may form an enantiopure self-assembly structure in such high dense coverage. A formation of a random mixture of the two chiral enantiomers may also lead to the disordered phase appearing achiral in STM …”
Section: Resultsmentioning
confidence: 99%
“…A formation of a random mixture of the two chiral enantiomers may also lead to the disordered phase appearing achiral in STM. 52 In order to understand the formation of chiral Co-DPP configurations, we investigate in more detail their appearances in STM images and their structure from DFT calculations (Figure 2). On the surface, isolated molecules are only found adsorbed at step edges, and they appear also as L-and R-Co-DPP as shown in Figure 2a.…”
Section: Stmmentioning
confidence: 99%